Capillary electrophoresis coupled to contactless conductivity detection for analysis of amino acids of agricultural interest in composting. Issue 19 (5th September 2016) - Cappelini, Luciana Teresa Dias; de Fátima Menegoci Eugênio, Patrícia; Leão, Paulo Augusto Gomes Carneiro; Alberice, Juliana Vieira; Urbaczek, Ana Carolina; Assunção, Nilson Antonio; Juliano, Luiz; Carrilho, Emanuel
Abstract : Composting is a sustainable approach to manage animal and vegetal waste generated in the Fundação Parque Zoológico de São Paulo. The resulting compost is often used in ZOO's premises as an organic fertilizer for the production of vegetables, which is further used to feed the animals. The composting product provides many forms of mineral and also amino acids (AA) that are absorbed by plants as nutrients. Since most amino acids absorb only slightly or not at all in the UV wavelengths, we developed a method for the determination of AA of agricultural interest in the composting samples. Due to the complexity of samples, we used ion exchange chromatography for the purification of AA prior to analysis. The proposed CZE‐C 4 D method allowed a separation of the AA in a short analysis time (less than 3.0 min), with great linearity (with R 2 ranging from 0.993 to 0.998). Using a BGE of 10 mmol/L TEA, reduction of high‐frequency noise and lower baseline fluctuations were obtained. The LOQ for the five AA were around 35 μmol/L, and were adequate for our purpose. In addition, the method showed good precision (RSD of peak area and migration time less than 1.55 and 1.16%, respectively).